Components of a Successful Model for Economic Empowerment of Rural Youth - Kumar, Anjani; Singh, Rashmi (Indian Journal of Extension Education, 2014)
Entrepreneurship development has been recognized essential factor, playing great role in agricultural sector in the era of  Liberalization, Privatization and Globalization, open competition and free market economy. Agro-based entrepreneurship activities among farmers, farm women and rural youth are vital in the context of generating gainful  employment, minimizing the regional disparities and development of socio economic condition. However, rural youth  lack in entrepreneurial traits like ability to identify opportunities (Satapathy and Mishra, 2011). It is necessary that rural  youth are mobilized to go for entrepreneurship activities as per their resources and market demand of the area, many youth  are interested to undertake such activities to earning, but the major problems faced by them are usually lack of skill,  financial support during establishment and finally marketing of the produce.Such entrepreneurship development among  rural youth can play a vital role in generating self employment there by reducing the unemployment, checking migration  from rural areas, batter use of locally available resources, balance regional disparities and reducing unrest among youth.  Kumar et.al. (2012) observed that through the network of KVKs lakhs of people are trained in vario us areas.Thus KVKs  can play a crucial role in promoting entrepreneurship among rural youth through customized trainings. As a part of study  of entrepreneurship development among rural youth of Gurgaon district in Haryana, Krishi Vigyan Kendra started a long  duration vocational programmes for rural youth & women science 1999. It is heartening to say that since then the KVK has  not looked back and had been organizing need based training course having potential for additional income and  employment generation and fitting well into eco-socio-cultural and technological system of their project area. Such need  based, standardized and well-planned course were conducted by KVK from 2000 to 2014 a period of 15 years. The  effectiveness of these training programmes assessed through evaluation and interaction with the farmers from time to time  and found quit an encouraging impact. Amongst the vocational course conducted at KVK, the Dairy farming, Beekeeping,  Dress designing & tailoring, Preservation of seasonal fruits and vegetables, custom service in Plant protection, Motor  winding and tractor repairing were found to be extremely popular and the overall adoption rate is 470. %. This experience  very strongly highlights the need for entrepreneurship development for self-empowerment to the rural youth and  strengthening the rural youth economy.
Keywords: Empowerment, Rural youth; Entrepreneurship development; Vocational trainings; Self empowerment generation; Market economy